Ultra-white glass and preparation method thereof
Through specific raw material combination and process processing, the bubble removal problem in ultra-white glass is solved, and the preparation of ultra-white glass with high transparency and excellent optical performance is achieved, improving the stability and performance of the glass.
Patent Information
- Application Number
- CN202510283516.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2045-03-11
AI Technical Summary
It is difficult to effectively remove bubbles during the preparation of existing ultra-white glasses, resulting in limited transparency and optical properties of glass, and existing clarified decolorizers may affect glass performance.
A specific raw material combination, including quartz sand, sodium carbonate, boronite, magnesium sand, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide, was used to melt the furnace, vacuum debubble and high-temperature insulation through the synergistic effect of strontium chloride, calcium fluoride, barium nitrate and zirconia, followed by calendering and annealing to prepare ultra-white glass with excellent whiteness and visible light transmittance.
It realizes the high transparency and excellent optical properties of ultra-white glass, improves the chemical stability, mechanical strength and compressive strength of the glass, and simplifies the process flow and makes the parameters easy to control.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass preparation, and specifically relates to ultra-white glass and a preparation method thereof. Background Art
[0002] Ultra-clear glass is a kind of ultra-transparent low-iron glass, also known as low-iron glass and high-transparency glass. It is a high-quality, multifunctional new high-end glass variety with a light transmittance of more than 91.5%. It has the characteristics of crystal clearness, high-end elegance, and is known as the "Crystal Prince" of the glass family.
[0003] Ultra-clear glass has all the processing properties of high-quality float glass, and has excellent physical, mechanical and optical properties. It can be processed in various ways like other high-quality float glass. The incomparable superior quality and product performance make ultra-clear glass have a broad application space and bright market prospects, but ultra-clear glass is difficult to process and prepare.
[0004] One of the important factors in glass quality is the bubbles in the glass. Glass is made by mixing raw materials such as silica sand, soda ash, quartz stone, etc., and then melting them at high temperature. The glass melted at high temperature is a high-viscosity liquid containing a large number of bubbles. When no clarifier is used, the bubbles contain the most carbon dioxide and nitrogen, which cannot be dissolved in the molten glass. If it simply relies on the bubbles rising to the surface of the glass and then bursting and releasing, it will take a lot of time and does not meet the requirements of industrial production.
[0005] Therefore, it is necessary to add a clarifying and decolorizing agent during the preparation of ultra-white glass. Currently, the most commonly used clarifying and decolorizing agents include Sb2O5, Sb2O3, and CuSO4. Among them, Sb2O5 and Sb2O3 may react with other components in the glass during the glass melting process, affecting the performance of the glass; and the use of CuSO4 will cause glass emulsification, that is, opaque milky white spots appear on the surface of the glass, affecting the transparency and optical properties of the glass. Therefore, the existing glass clarifying and decolorizing agents still need to be improved in terms of improving the transmittance of ultra-white glass and eliminating bubbles. Summary of the invention
[0006] The purpose of the present invention is to provide an ultra-white glass, which has good whiteness and visible light transmittance; the present invention also provides a preparation method thereof.
[0007] The ultra-white glass of the present invention is composed of the following raw materials, measured by weight: 110 parts of quartz sand, 18-20 parts of sodium carbonate, 14-16 parts of colemanite, 4.5-5.5 parts of magnesia, 2.6-2.8 parts of calcined aluminum oxide, 1.1-1.3 parts of potassium oxide, 0.8-1.0 parts of zinc oxide, 1.5-1.7 parts of phosphorus pentoxide, 0.15-0.20 parts of strontium chloride, 0.3-0.34 parts of calcium fluoride, 0.25-0.27 parts of barium nitrate and 0.16-0.18 parts of zirconium oxide.
[0008] in: The chemical composition of the quartz sand, in terms of mass percentage, is as follows: SiO2 99.57%, Al2O3 0.21%, Fe2O3 0.0075%, and the loss on ignition is 0.2125%.
[0009] The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO2 0.43%, Fe2O3 0.37%, Al2O3 0.38%, and the loss on ignition is 0.15%.
[0010] The chemical composition of the calcined alumina, in terms of mass percentage, is as follows: Al2O3 99.72%, Na2O 0.20%, and loss on ignition 0.08%.
[0011] The method for preparing ultra-white glass of the present invention comprises the following steps: (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuum and degas for 8-10 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature is raised to 580-600°C, continue to raise the temperature to 1530-1550°C and keep the temperature for 8.2-8.3 hours to obtain glass liquid; (2) The glass liquid is fed into a calender for calendering; (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
[0012] in: The temperature of the calendering process in step (2) is 1150-1180°C.
[0013] The annealing treatment in step (3) is to first cool the temperature to 520-530°C at a rate of 3.8-4.0°C / min and keep it at that temperature for 30-40 minutes, then cool the temperature to 320-330°C at a rate of 2.5-2.8°C / min, and finally cool naturally to room temperature.
[0014] Compared with the prior art, the present invention has the following beneficial effects: (1) The ultra-white glass described in the present invention is mainly composed of quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina and potassium oxide, and zinc oxide and phosphorus pentoxide are also added. The introduction of alumina through calcined alumina reduces the expansion coefficient of the glass, thereby improving the chemical stability and mechanical strength of the glass. The introduction of magnesium oxide through magnesia reduces the crystallization tendency and hardening speed of the glass, thereby improving the forming properties of the glass. The introduction of sodium oxide through sodium carbonate can greatly reduce the viscosity of the glass liquid. In addition, K2O can increase the transparency and gloss of the glass. The introduction of calcium oxide and boron trioxide through colemanite can promote the formation of silicate structure in the glass, increase the density and hardness of the glass, and boron trioxide forms a strong network in the glass structure, thereby improving the hardness and compressive strength of the glass. When zinc oxide is added to glass as a network modifier, it can improve the chemical stability of the glass while lowering the melting temperature of the glass. In addition, it can reduce the thermal expansion coefficient of the glass, enhance the deformation resistance of the glass and increase the whiteness of the glass. Phosphorus pentoxide can enhance the light transmittance of the glass in the ultraviolet region and also increase the dispersion coefficient of the glass. The raw materials interact with each other to ensure the stability and transmittance of ultra-white glass.
[0015] (2) The ultra-white glass of the present invention uses a mixture of strontium chloride, calcium fluoride, barium nitrate and zirconium oxide as a clarifying and decolorizing agent, and the four have a synergistic effect. Among them, strontium chloride is decomposed by heat during the glass melting process to produce chlorine and other gases. The fluoride ions produced by the decomposition of calcium fluoride can react with SiO2 in the glass to produce volatile fluorides, thereby reducing the viscosity of the glass melt. These gases form tiny bubbles in the glass melt, and the bubbles rise by buoyancy and carry other gases out, thereby reducing the bubbles in the glass. Barium nitrate decomposes during the glass melting process to produce oxygen, nitric oxide and nitrogen dioxide, thereby improving the clarification effect. The types of gases produced by the decomposition of strontium chloride, calcium fluoride and barium nitrate are different and the temperatures of the released gases are different. The temperatures of the gases produced by the decomposition of the three cover the entire process of glass melting, including the glass liquid formation process and the glass liquid clarification process. In addition, since the gases formed are different and of many types, it is beneficial to increase the partial pressure of the gas with a lower partial pressure in the original bubble, promote the precipitation of other component gases dissolved in the glass liquid into the bubble, so that the bubble grows and precipitates. Zirconia has good chemical stability and can remain stable in glass melt, significantly reducing the viscosity of glass melt, making bubbles easier to merge and float, thereby accelerating the clarification process. In addition, the addition of zirconium oxide can significantly increase the refractive index of glass and reduce dispersion, thereby improving the optical properties of glass.
[0016] (3) The method for preparing the ultra-white glass of the present invention has a simple process and easy-to-control parameters. The prepared ultra-white glass has excellent whiteness and visible light transmittance. DETAILED DESCRIPTION
[0017] The present invention is further described below with reference to the embodiments.
[0018] Example 1 The ultra-white glass described in this embodiment 1 is composed of the following raw materials, measured by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.18 parts of strontium chloride, 0.32 parts of calcium fluoride, 0.26 parts of barium nitrate, and 0.17 parts of zirconium oxide.
[0019] in: The chemical composition of the quartz sand, in terms of mass percentage, is as follows: SiO2 99.57%, Al2O3 0.21%, Fe2O3 0.0075%, and the loss on ignition is 0.2125%.
[0020] The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO2 0.43%, Fe2O3 0.37%, Al2O3 0.38%, and the loss on ignition is 0.15%.
[0021] The chemical composition of the calcined alumina, in terms of mass percentage, is as follows: Al2O3 99.72%, Na2O 0.20%, and loss on ignition 0.08%.
[0022] The method for preparing the ultra-white glass described in this embodiment 1 comprises the following steps: (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuumize and degas for 9 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature reaches 590°C, continue to heat to 1540°C and keep the temperature for 8.25 hours to obtain glass liquid; (2) The glass liquid is fed into a calender for calendering; (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
[0023] in: The temperature of the calendering process in step (2) is 1165°C.
[0024] The annealing treatment in step (3) is to first cool the temperature to 525°C at a rate of 3.9°C / min and keep the temperature for 35 minutes, then cool the temperature to 325°C at a rate of 2.6°C / min, and finally cool naturally to room temperature. The whiteness of the ultra-white glass prepared in Example 1 is 0.061F, and the visible light transmittance is 96.1%.
[0025] Example 2 The ultra-white glass described in this Example 2 is composed of the following raw materials, in parts by weight: 110 parts of quartz sand, 20 parts of sodium carbonate, 14 parts of colemanite, 4.5 parts of magnesia, 2.8 parts of calcined alumina, 1.1 parts of potassium oxide, 1.0 parts of zinc oxide, 1.7 parts of phosphorus pentoxide, 0.15 parts of strontium chloride, 0.34 parts of calcium fluoride, 0.27 parts of barium nitrate, and 0.18 parts of zirconium oxide.
[0026] in: The chemical composition of the quartz sand, in terms of mass percentage, is as follows: SiO2 99.57%, Al2O3 0.21%, Fe2O3 0.0075%, and the loss on ignition is 0.2125%.
[0027] The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO2 0.43%, Fe2O3 0.37%, Al2O3 0.38%, and the loss on ignition is 0.15%.
[0028] The chemical composition of the calcined alumina, in terms of mass percentage, is as follows: Al2O3 99.72%, Na2O 0.20%, and loss on ignition 0.08%.
[0029] The method for preparing the ultra-white glass described in Example 2 comprises the following steps: (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuumize and degas for 8 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature reaches 580°C, continue to heat to 1530°C and keep the temperature for 8.2 hours to obtain glass liquid; (2) The glass liquid is fed into a calender for calendering; (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
[0030] in: The temperature of the calendering process in step (2) is 1150°C.
[0031] The annealing treatment in step (3) is to first cool the temperature to 520°C at a rate of 3.8°C / min and keep the temperature for 30 minutes, then cool the temperature to 320°C at a rate of 2.5°C / min, and finally cool naturally to room temperature. The whiteness of the ultra-white glass prepared in Example 2 is 0.066F, and the visible light transmittance is 94.7%.
[0032] Example 3 The ultra-white glass described in this Example 3 is composed of the following raw materials, in parts by weight: 110 parts of quartz sand, 18 parts of sodium carbonate, 16 parts of colemanite, 5.5 parts of magnesia, 2.6 parts of calcined alumina, 1.3 parts of potassium oxide, 0.8 parts of zinc oxide, 1.5 parts of phosphorus pentoxide, 0.20 parts of strontium chloride, 0.3 parts of calcium fluoride, 0.25 parts of barium nitrate, and 0.16 parts of zirconium oxide.
[0033] in: The chemical composition of the quartz sand, in terms of mass percentage, is as follows: SiO2 99.57%, Al2O3 0.21%, Fe2O3 0.0075%, and the loss on ignition is 0.2125%.
[0034] The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO2 0.43%, Fe2O3 0.37%, Al2O3 0.38%, and the loss on ignition is 0.15%.
[0035] The chemical composition of the calcined alumina, in terms of mass percentage, is as follows: Al2O3 99.72%, Na2O 0.20%, and loss on ignition 0.08%.
[0036] The method for preparing the ultra-white glass described in this embodiment 3 comprises the following steps: (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuumize and degas for 10 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature reaches 600°C, continue to heat to 1550°C and keep the temperature for 8.3 hours to obtain glass liquid; (2) The glass liquid is fed into a calender for calendering; (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
[0037] in: The temperature of the calendering process in step (2) is 1180°C.
[0038] The annealing treatment in step (3) is to first cool the temperature to 530°C at a rate of 4.0°C / min and keep the temperature for 40 minutes, then cool the temperature to 330°C at a rate of 2.8°C / min, and finally cool naturally to room temperature. The whiteness of the ultra-white glass prepared in Example 3 is 0.064F, and the visible light transmittance is 95.3%.
[0039] Comparative Example 1 The preparation method of the ultra-white glass described in this comparative example 1 is the same as that of Example 1, the only difference being that the raw material composition is different. The ultra-white glass described in this comparative example 1 is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.32 parts of calcium fluoride, 0.26 parts of barium nitrate, and 0.17 parts of zirconium oxide. The whiteness of the ultra-white glass prepared in comparative example 1 is 0.36F, and the visible light transmittance is 91.5%.
[0040] Comparative Example 2 The preparation method of the ultra-white glass described in this comparative example 2 is the same as that of Example 1, the only difference being that the raw material composition is different. The ultra-white glass described in this comparative example 2 is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.18 parts of strontium chloride, 0.26 parts of barium nitrate, and 0.17 parts of zirconium oxide. The whiteness of the ultra-white glass prepared in comparative example 2 is 0.55F, and the visible light transmittance is 85.8%.
[0041] Comparative Example 3 The preparation method of the ultra-white glass described in this comparative example 3 is the same as that of Example 1, the only difference being that the raw material composition is different. The ultra-white glass described in this comparative example 3 is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.18 parts of strontium chloride, 0.32 parts of calcium fluoride, and 0.17 parts of zirconium oxide. The whiteness of the ultra-white glass prepared in comparative example 3 is 0.41F, and the visible light transmittance is 88.4%.
[0042] Comparative Example 4 The preparation method of the ultra-white glass described in this comparative example 4 is the same as that of Example 1, the only difference being that the raw material composition is different. The ultra-white glass described in this comparative example 4 is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 19 parts of sodium carbonate, 15 parts of colemanite, 5.0 parts of magnesia, 2.7 parts of calcined alumina, 1.2 parts of potassium oxide, 0.9 parts of zinc oxide, 1.6 parts of phosphorus pentoxide, 0.18 parts of strontium chloride, 0.32 parts of calcium fluoride, and 0.26 parts of barium nitrate. The whiteness of the ultra-white glass prepared in comparative example 4 is 0.23F, and the visible light transmittance is 92.2%.
Claims
1. An ultra-white glass, characterized in that: The invention is composed of the following raw materials in parts by weight: 110 parts of quartz sand, 18-20 parts of sodium carbonate, 14-16 parts of colemanite, 4.5-5.5 parts of magnesia, 2.6-2.8 parts of calcined alumina, 1.1-1.3 parts of potassium oxide, 0.8-1.0 parts of zinc oxide, 1.5-1.7 parts of phosphorus pentoxide, 0.15-0.20 parts of strontium chloride, 0.3-0.34 parts of calcium fluoride, 0.25-0.27 parts of barium nitrate and 0.16-0.18 parts of zirconium oxide.
2. The ultra-white glass according to claim 1, characterized in that: The chemical composition of the quartz sand, in terms of mass percentage, is as follows: SiO2 99.57%, Al2O3 0.21%, Fe2O3 0.0075%, and the loss on ignition is 0.2125%.
3. The ultra-white glass according to claim 1, characterized in that: The chemical composition of the magnesia is as follows, in terms of mass percentage: MgO 97.85%, CaO 0.82%, SiO2 0.43%, Fe2O3 0.37%, Al2O3 0.38%, and loss on ignition is 0.15%.
4. The ultra-white glass according to claim 1, characterized in that: The chemical composition of the calcined alumina, in terms of mass percentage, is as follows: Al2O3 99.72%, Na2O 0.20%, and loss on ignition 0.08%.
5. A method for preparing the ultra-white glass according to claim 1, characterized in that: It consists of the following steps: (1) Add quartz sand, sodium carbonate, colemanite, magnesia, calcined alumina, potassium oxide, zinc oxide and phosphorus pentoxide into a kiln for melting, vacuum and degas for 8-10 minutes, then add strontium chloride, calcium fluoride, barium nitrate and zirconium oxide when the temperature is raised to 580-600°C, continue to raise the temperature to 1530-1550°C and keep the temperature for 8.2-8.3 hours to obtain glass liquid; (2) The glass liquid is fed into a calender for calendering; (3) The formed glass is annealed in an annealing kiln to produce ultra-white glass.
6. The method for preparing ultra-white glass according to claim 5, characterized in that: The temperature of the calendering process in step (2) is 1150-1180°C.
7. The method for preparing ultra-white glass according to claim 5, characterized in that: The annealing treatment in step (3) is to first cool the temperature to 520-530°C at a rate of 3.8-4.0°C / min and keep it at that temperature for 30-40 minutes, then cool the temperature to 320-330°C at a rate of 2.5-2.8°C / min, and finally cool naturally to room temperature.
Citation Information
Patent Citations
Ultraviolet-resistant ultra-white rolled glass with high transmittance and production process
CN108516680A
Alkali-free aluminosilicate glass clarifying agent and preparation method of glass
CN113173702A
High-transparency glass bottle and preparation method thereof
CN115010362A
Ultra-white transparent glass and preparation method thereof
CN118239679A
Cited By
Aluminosilicate glass material based on calcined alpha-Al2O3 and preparation method thereof
CN120136426A
Electronic ceramic material based on calcined alpha-Al2O3 and preparation method thereof
CN120247537A
An electronic ceramic material based on calcined α-Al2O3 and its preparation method
CN120247537B
Ultra-white and ultra-thick float glass and preparation method thereof
CN120364948A
Ultra-clear and ultra-thick float glass and preparation method thereof
CN120364948B